Clinical Outcomes of Periodontal Surgery Following Crown Reduction for Malocclusion-Associated Gingival Recession in Cats - Kue Hwan Choe; Gyumin Kim; Seong Soo Kang; Se Eun Kim; Hyun Min Jo (Veterinary Sciences, 2026)
Gingival recession from traumatic occlusal contact commonly affects feline mandibular premolars and molars. Although crown reduction is routinely performed to eliminate traumatic occlusal forces, its ability to restore established periodontal defects remains unclear. This study evaluated whether adjunctive periodontal surgery provides additional clinical benefits following crown reduction. This retrospective study included 17 cats (34 teeth) with malocclusion-associated gingival recession. Treatment grouping was performed at the tooth level, with one cat contributing teeth to both the Control and Group A. Teeth were classified into three groups: no treatment (Control), crown reduction alone (Group A), and crown reduction with adjunctive periodontal surgery (Group B). Gingival recession, clinical attachment level (CAL), root coverage, and the vertical bone defect ratio (VBDR) were evaluated before and after treatment. Between-group differences were analyzed using linear mixed-effects models. Control showed no significant changes. Both treatment groups showed significant improvements in gingival recession, CAL, and VBDR. Compared with crown reduction alone, adjunctive surgery yielded significantly greater CAL improvement, radiographic bone healing, and overall clinical success rate (91.7% in Group B vs. 25.0% in Group A), though root coverage did not differ significantly. Traumatic occlusion elimination is foundational for managing feline malocclusion-associated gingival recession. However, adjunctive periodontal surgery enhances periodontal recovery and overall success, offering a valuable tooth-preserving option when complete reconstruction is required.